Plicae: Where Do They Come from and When Are They Relevant? - Wong, Jenn Shiunn; Lalam, Radhesh (Seminars in Musculoskeletal Radiology, 2019)
Synovial plicae are vestigial folds of synovium in a joint, most widely recognized in the knee and also in the elbow and hip joints. The most commonly shared theory on the origin of plicae is that they are the remnants of the membranes that divide the synovial cavitations during normal joint development. Synovial folds do not generally cause any symptoms. However, they can become inflamed, thickened, fibrosed, and also impinged in the joint, leading to mechanical symptoms and chondral damage. This article presents an overview of the embryological origin of plicae, their anatomy, pathologies, and appearances on imaging. We also discuss the lesser known plicae in various other areas.
Keywords: plica; synovial fold; plica syndrome